US elections and European cohesion: Scenarios for green transitions and transatlantic climate action - Rachel Tausendfreund; Mareike Moraal; Loyle Campbell (Heinrich-Böll-Stiftung, 2024)
The Biden administration has been arguably the greenest in US history, but the polls show that there's about a fifty-fifty chance that he will be followed by one of the least climate-friendly presidents. So this November, the choice at the ballot box will be a stark one for climate policies, with Kamala Harris likely to push for a green transition and climate justice, and Donald Trump expected to end climate measures and focus on energy supply and energy independence. Given this context, this paper explores how the EU and its member states could adjust their climate policies, depending on the outcome of the US election. We plot out potential Harris and Trump administration positions on two key elements of global climate action and possible European responses along the variables of unity and decisiveness. – – Die Regierung Biden war wohl die grünste in der Geschichte der USA, aber die Umfragen zeigen, dass die Wahrscheinlichkeit, dass auf ihn einer der am wenigsten klimafreundlichen Präsidenten folgen wird, etwa fünfzig zu fünfzig beträgt. Kamala Harris wird sich wahrscheinlich für einen grünen Wandel und Klimagerechtigkeit einsetzen, während Donald Trump voraussichtlich die Klimamaßnahmen beenden und sich auf Energieversorgung und Energieunabhängigkeit konzentrieren wird. Vor diesem Hintergrund wird in diesem Papier (englisch) untersucht, wie die EU und ihre Mitgliedstaaten ihre Klimapolitik in Abhängigkeit vom Ausgang der US-Wahl anpassen könnten. Wir stellen mögliche Positionen der Harris- und Trump-Administration zu zwei Schlüsselelementen globaler Klimamaßnahmen und mögliche europäische Antworten entlang der Variablen Einheit und Entschlossenheit dar.
Keywords: 330; Climate; Klima; Green (Industrial) Domestic Policies; Grüne (Industrie-)Politik im Inland; International Climate Agenda; Internationale Klima-Agenda; Kamala Harris; Donald Trump; European Union (EU); Europäische Union (EU); United States of America (USA); Vereinigte Staaten von Amerika (USA)